2021
DOI: 10.7759/cureus.19691
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Thromboprophylaxis Post-Orthopedic Surgery

Abstract: Given the high risk of venous thromboembolism (VTE) post-orthopedic surgery and the vital role of thromboprophylaxis in preventing VTEs, this meta-analysis aimed to assess the efficacy of thromboprophylaxis post major orthopedic surgery and the relevant safety measures. In this review, we conducted a computer-aided search of Google Scholar, PubMed, CINAHL, Cochrane, Medline, and EMBASE databases. We included all published randomized clinical trials (RCTs) that utilized enoxaparin, fondaparinux, dabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…They are the most commonly used and effective anticoagulants for the prevention and treatment of various thromboembolic diseases. This study found that there was no statistically signi cant difference in the treatment effect and DVT incidence among patients in LMWH group, FPX group, and Rivaroxaban group, indicating that three groups of anticoagulants can all reduce the incidence of VTE after THA, which was consistent with the research conclusion of Alsheikh K, et al [17]. However, in terms of treatment cost ratio, the FPX group was signi cantly higher than the other two groups, indicating that LMWH and Rivaroxaban were more economical than FPX; For the portability of drug use for patients, Rivaroxaban can be taken orally directly compared with LMWH and FPX, which is more convenient and faster, and reduce the complications of injection pain, infection, poor compliance caused by subcutaneous injection [18].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They are the most commonly used and effective anticoagulants for the prevention and treatment of various thromboembolic diseases. This study found that there was no statistically signi cant difference in the treatment effect and DVT incidence among patients in LMWH group, FPX group, and Rivaroxaban group, indicating that three groups of anticoagulants can all reduce the incidence of VTE after THA, which was consistent with the research conclusion of Alsheikh K, et al [17]. However, in terms of treatment cost ratio, the FPX group was signi cantly higher than the other two groups, indicating that LMWH and Rivaroxaban were more economical than FPX; For the portability of drug use for patients, Rivaroxaban can be taken orally directly compared with LMWH and FPX, which is more convenient and faster, and reduce the complications of injection pain, infection, poor compliance caused by subcutaneous injection [18].…”
Section: Discussionsupporting
confidence: 87%
“…However, due to the lack of consistency in the de nition of "bleeding", makes it di cult to explain the true balance of advantages and disadvantages. A large number of studies have shown that [19][20], LMWH, FPX, and Rivaroxaban have no signi cant differences in VTE-related mortality, massive hemorrhage, and adverse events. The three drugs have good safety and effectiveness in the prevention and treatment of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The use of aspirin remains controversial although it is now recommended in several VTE clinical guidelines when used as part of a comprehensive VTE prophylaxis program. VTE, SSI and bleeding outcomes for aspirin prophylaxis have been shown to be no different to potent anticoagulants 18 20 . However other studies have reported aspirin is associated with an increased incidence of DVT and wound complications, but a lower risk of bleeding 21 23 .…”
Section: Discussionmentioning
confidence: 99%
“…These include agents that prevent platelet activation, aggregation, and/or adhesion, known as antiplatelets, and others that inhibit clotting factors, known as anticoagulants. When choosing a pharmacological thromboprophylaxis agent for patients undergoing major lower-extremity orthopedic procedures, who possess a low risk of bleeding, factors such as the specific type of surgery and comorbidities play a role in the decision-making process [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Current Methodsmentioning
confidence: 99%
“…In cases when UFH injections are undesirable, warfarin may be considered as an alternative option. Nevertheless, it is important to note that patients with heparin-induced thrombocytopenia (HIT) or a history of HIT should be treated with a non-heparin agent [ 3 , 4 , 5 , 6 , 7 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Current Methodsmentioning
confidence: 99%